The effect of Pandanus conoideus Lam. oil on pancreatic (i-cells and glibenclamide hypoglycemic effect of diabetic Wistar rats - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Background: Oxidative stress has been implicated in pathogenesis and progression of many degenerative disorders including naturally occuring and chemically-induced diabetes mellitus. In addition to the increased production of free radicals, antioxidant defense systems are disturbed in diabetes mellitus. As a result, oxidative stress may cause oxidative damage of cellular, including Ii-cells of pancreas. Objective: This study was aimed at investigating the effect of P. eonoideus Lam. on hypoglycemic activity of glibenclamide and histochemical changes in pancreatic islets. Methods: Thirty male Rattus norvegicus rats were used in the study, and randomly selected. The animals were divided into two groups, each group consisted of 15 rats. Each group was devided into 3 subgroups, the first subgroups were subgroup 1